'I play with the baby so that people can see that I'm a man': Young fathers' involvement in the first 1 000 days of a child's life in South Africa. Issue 1 (2nd January 2017) - Gibbs, Andrew; Crankshaw, Tamaryn; Lewinsohn, Rebecca; Chirawu, Petronella; Willan, Samantha
ABSTRACT: There is a growing focus on men's involvement in the first 1 000 days of a child's life (i.e. conception through to two years of age). Men's involvement is understood to improve child health and as a pathway to gender equality. We sought to understand the forms of care and support men provided during the first 1 000 days of a child's life in an urban informal settlement in Durban, South Africa. We conducted in-depth interviews with 20 men and 15 women and three focus groups with men to understand men's involvement. Men and women described multiple ways in which men were involved in care and support during the first 1 000 days and reasons supporting and hindering this. In contrast to much literature that situates men's involvement in care as intrinsically gender equitable, we argue that while men do become involved in care and support, it is not linked to a wider commitment to gender equity. Rather it bolsters a relatively conservative understanding of masculinity, linked to the establishment of a household. Where men do not become involved in care, this is linked to men seeking to retain a more youthful masculinity. We suggest interventions working with men to increase caregiving need to engage around transforming gender norms.